Efektivitas Penyaluran dana Wakaf dalam Upaya Pengembangan Usaha Mikro Sebelum dan Selama Pandemi COVID-19 - Nurani, Zuhda Elfairuza; Vahlevi, Dewi Riza Lisvi (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
Thesis entitled "The Effectiveness of Cash Waqf Fund Distribution through our Empowered Program in efforts to Develop Micro-Enterprises Before and During the Covid-19 Pandemic (Analytical Study at KSPPS BMT Permata Jawa Timur, Mojokerto)" is dotted with the framework of thinking that the effectiveness of cash waqf in institutions that manage waqf is an important benchmark in the welfare of the community. The purpose of the study was to determine the mechanisms, analyses in the effectiveness of cash waqf disbursements in the development of micro-enterprises before and during covid-19. This study uses a comparative qualitative descriptive approach by comparing between two variables. Using effectiveness benchmarks according to Campbel Theory. The results of the study obtained that through the mechanism of disbursement of cash waqf funds, namely the source of cash waqf funds, the identification of prospective members and the stages of disbursement of funds, referring to the benchmarks of effectiveness, understanding of risks and the realization of The Standard Operating Procedures (SOP) in KSPPS BMT Permata can be concluded that the effectiveness of the distribution of cash waqf programs we empowered before the pandemic can be said to be very effective and during the Covid-19 pandemic it is said to be less effective, but KSPPS BMT Permata has a strategy to be able to survive risks in the midst of a pandemic.